TRAIL induces pro-apoptotic crosstalk between the TRAIL-receptor signaling pathway and TrkAIII in SH-SY5Y cells, unveiling a potential therapeutic “Achilles heel” for the TrkAIII oncoprotein in neuroblastoma - Gneo, Luciana (Oncotarget, 2016)
TrkAIII expression in neuroblastoma (NB) associates with advanced stage disease, worse prognosis, post therapeutic relapse, and in NB models TrkAIII exhibits oncogenic activity and promotes chemotherapeutic-resistance. Here, we report a potential therapeutic “Achilles heel” for the TrkAIII oncoprotein in a SH-SY5Y NB model that is characterised by one-way TRAIL-induced, pro-apoptotic crosstalk between the TRAIL receptor signaling pathway and TrkAIII that results in the delayed induction of apoptosis. In TrkAIII SH-SY5Y cells, blocked in the intrinsic apoptosis pathway by elevated constitutive Bcl-2, Bcl-xL and Mcl-1 expression, TRAIL induced delayed caspase-dependent apoptosis via the extrinsic pathway and completely abrogated tumourigenic capacity in vitro. This effect was initiated by TRAIL-induced SHP-dependent c-Src activation, the induction of TrkAIII/SHP-1/c-Src complexing leading to SHP-mediated TrkAIII de-phosphorylation, subsequent induction of complexing between de-phosphorylated TrkAIII and cFLIP associated with a time-dependent increase the caspase-8 to cFLIP ratio at activated death receptors, resulting in delayed caspase cleavage and caspase-dependent apoptosis. We also confirm rate-limiting roles for c-FLIP and Mcl-1 in regulating the sensitivity of TrkAIII SH-SY5Y cells to TRAIL-induced apoptosis via the extrinsic and intrinsic pathways, respectively. Our study unveils a novel mechanism for the TRAIL-induced apoptosis of TrkAIII expressing NB cells that depends upon SHP/Src-mediated crosstalk between the TRAIL-receptor signaling pathway and TrkAIII, and supports a novel potential pro-apoptotic therapeutic use for TRAIL in TrkAIII expressing NB.